1997
DOI: 10.1111/j.1749-6632.1997.tb48335.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐period Comets and the Oort Cloud

Abstract: The long‐period comets pose a unique problem for the impact hazard problem. Because of their very long orbital periods and generally large distances from the Sun, they cannot be surveyed and catalogued in the same manner as the near‐Earth asteroids and short‐period comets. They appear at random, uniformly distributed on the celestial sphere. Current technologies can detect long‐period comets at distances of ∼5 AU, giving somewhat less than a one year warning time for potential Earth impactors. The mean impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 73 publications
(93 reference statements)
1
12
0
Order By: Relevance
“…Recent calculations imply formation of s 450 terrestrial craters of D s 100 km since the late heavy bombardment, and cratering rate estimates suggest that a large 200 km crater may occur every 150 Ma and a 500 km crater every 450 Ma [40,41]. Similar impact rates are implied independently by studies of comets and for the combined probabilities of comets and asteroids ; Weissman [42] indicates that the impact probability of long-period comets large enough to produce craters s 10 km is about 1 Myr 31 and estimates an interval of 1.7U10 7 yr between potentially catastrophic long-period comet impacts. Both comets and asteroids cause impacts, but comets can have much higher velocities [43].…”
Section: Discussionmentioning
confidence: 73%
“…Recent calculations imply formation of s 450 terrestrial craters of D s 100 km since the late heavy bombardment, and cratering rate estimates suggest that a large 200 km crater may occur every 150 Ma and a 500 km crater every 450 Ma [40,41]. Similar impact rates are implied independently by studies of comets and for the combined probabilities of comets and asteroids ; Weissman [42] indicates that the impact probability of long-period comets large enough to produce craters s 10 km is about 1 Myr 31 and estimates an interval of 1.7U10 7 yr between potentially catastrophic long-period comet impacts. Both comets and asteroids cause impacts, but comets can have much higher velocities [43].…”
Section: Discussionmentioning
confidence: 73%
“…However, comets with dimensions of tens of meters will disintegrate at high altitude. Weissman (59) estimated that a comet would have to be >350 m in diameter to penetrate Earth's atmosphere and form a crater, depending upon angle, velocity, etc. Such an event would be at least 500 × more energetic than the Tunguska event.…”
Section: Discussionmentioning
confidence: 99%
“…Weissman (1997) calculates that 27% of long-period comets are lost to "random disruption." The reason these comets fall apart is not clear; Weissman (1997) suggested that is associated with the heating of the nucleus during perihelion passage. That the probability of disruption is greatest on the first perihelion passage is attributed to a selection effect that removes those objects that are weakest first.…”
Section: Evidence Of Weak Interplanetary Materialsmentioning
confidence: 99%
“…Weissman (1997) noted that the mean infall velocity of long-period comets is 51.8 km s 21 and that the energyweighted mean velocity is 57.7 km s 21 .…”
Section: Evidence Of Weak Interplanetary Materialsmentioning
confidence: 99%
See 1 more Smart Citation